PENGARUH BAHAN DAN DOSIS KOMPOS CAIR TERHADAP PERTUMBUHAN SELADA (Lactuca sativa sp.) (The Effect Of Material And Dosages Of Liquid Organic Fertilizers On Lettuce (Lactuca sativa Sp.) Growth) - Made Deviani Duaja (Bioplantae, 2012)
The aim of this research was to examine the effect of different material and dosages of liquid organic fertilizer on growth and yield of lettuce. The experiment was conducted at Agriculture farm, Jambi University. The laboratory analysis of soil and plant was conducted at Agriculture Laboratory and material of organic fertilizers in BALITRO, Bogor. Research design used factorial, arranged with randomized complete block designed. The treatment are Factor I material of organic compost liquid, control (p0), Imperata cylindrica (p1), Cromolaena odorata (p2) and Leucena lecochepala (p3), and the second factor are dosage, control (d0), 5 ml (d1), 10 ml (d2) and 15 ml (d3). Result showed that there was interaction affect between liquid compost material and dosage on growth parameter, number of leaves, leaf area, plant height, fresh weight dan plant yield. The trend of growth parameter indicated that compost material Cromolaena odorata at dosage 15 ml showed the highest. The same result was achieved at lettuce yield. However, in this research the optimum combination of liquid compost material and dosage was not yet attainable.Key words: Fertilizers, lettuce, cromolaena, leucena, imperata